Evaluating future U.S. Army force posture in Europe : Phase I report - Samp, Lisa Sawyer (CSIS report., 2016)
"This report offers a re-examination of U.S. Army force posture in Europe amid heightened tensions between the United States and Russia over the geopolitical orientation of Ukraine. This study reviews Russian military capabilities; considers alternative U.S. force posture arrangements; assesses how to determine whether assurance and deterrence goals are being met; and offers concrete recommendations in order to optimize the U.S. Army's presence in Europe to deter Russian aggression against the most vulnerable NATO members"--Publisher's web site